Students' Perception of Practical Activities in Biology Laboratory SMAN 2 Painan - Elifia Zulfa Endela; Vauzia Vauzia; Ganda Hijrah Selaras; Armen Armen (Universitas Negeri Padang, 2019)
This study aims to determine student’s perceptions of SMAN 2 Painan, because it has not been examined how students think about practicum. The type of research is descriptive and used quantitative approachment. The population of this study was class XI sain of SMA 2 Painan with propotional random sampling technique. The sample was 60 students.Thedatacollection techniqethrough representatives, observation and, questionnaires. The results showed that the practicum preparation of students was good74.80%, the implementation of students was very good 83.00% and the practical closing stage of students was good 79.00%.